Act and crime the philosophy of action and its implications for criminal law - Moore, Michael S., 1943- (Oxford : Oxford University Press, 2010)
What implications are there for the criminal law from the philosophy of action? Providing a unified account of the theory of action presupposed by both Anglo-American criminal law and the morality that underlies it, Moore develops a coherent theory of action in philosophy and assesses its effects on criminal law.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 9, 2010).
Keywords: Criminal act; Criminal liability; Criminal law -- Philosophy